2020
DOI: 10.1038/s41598-020-74811-5
|View full text |Cite|
|
Sign up to set email alerts
|

Quantifying the distribution of protein oligomerization degree reflects cellular information capacity

Abstract: The generation of information, energy and biomass in living cells involves integrated processes that optimally evolve into complex and robust cellular networks. Protein homo-oligomerization, which is correlated with cooperativity in biology, is one means of scaling the complexity of protein networks. It can play critical roles in determining the sensitivity of genetic regulatory circuits and metabolic pathways. Therefore, understanding the roles of oligomerization may lead to new approaches of probing biologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 60 publications
0
12
0
1
Order By: Relevance
“…While some proteins exhibit several oligomeric forms [8][9][10] , for most proteins only one possible assembly is indicated. A recent study showed that in E.coli about a quarter of proteins with known structure are monomeric, close to half are dimeric and the rest have higher oligomeric states 11 . However, that study, as well as many others, rely on the quaternary state that is indicated in UniProt or the PDB.…”
Section: Introductionmentioning
confidence: 99%
“…While some proteins exhibit several oligomeric forms [8][9][10] , for most proteins only one possible assembly is indicated. A recent study showed that in E.coli about a quarter of proteins with known structure are monomeric, close to half are dimeric and the rest have higher oligomeric states 11 . However, that study, as well as many others, rely on the quaternary state that is indicated in UniProt or the PDB.…”
Section: Introductionmentioning
confidence: 99%
“…S5B). In addition, the IGs were enriched for proteins that form homo oligomers (p < 0.0001, chi-square test, 2.7 fold enrichment, table S2), according to calculations based on the Uniprot database and a recent genome-wide oligomerization estimation ( 54 ). Hetero-oligomerization is probably also a driving force for the IGs, but to our knowledge, no comparative study has been performed.…”
Section: Resultsmentioning
confidence: 99%
“…And the C 2 H 2 domains of Traes_3AS_BE15533CD.1 /2 (Z1;D)-C 2 H 2 domains are completely different from its variant Traes_3AS_BE15533CD.3 (M3-C 2 H 2 domain). Undoubtedly, different splice variants of a TaC 2 H 2 -ZF gene have different number or type C 2 H 2 domains, may perform different functions [ 26 ]. For the detailed information of the classified C 2 H 2 -ZFPs in T. aestivum , see Additional file 1 : Table S1.…”
Section: Resultsmentioning
confidence: 99%